Insights into the intestinal microbiota of Exopalaemon annandalei and Exopalaemon carinicauda in the Yangtze River estuary - Wang, Jiahao; Feng, Guangpeng; Han, Zhiqiang; Zhang, Tao; Chen, Jinhui; Wu, Jianhui (Frontiers in Cellular and Infection Microbiology, 2024)
Summary: The gut microbiota plays a crucial role in food webs, carbon cycling, and related elements. Exopalaemon annandalei and Exopalaemon carinicauda are two important forage species in the Yangtze River estuary with extremely similar living habits and morphological characteristics. Exploring the microorganisms in the guts of these two shrimp species can help us understand the survival status of forage species and gut microbiota in the Yangtze River estuary. Therefore, this study analyzed the similarities and differences in the intestinal flora of E. annandalei and E. carinicauda through high-throughput sequencing of 16S rRNA gene amplicons. The results showed that the dominant bacteria in the intestinal flora of E. annandalei and E. carinicauda at the phylum level were Proteobacteria and Firmicutes, respectively. At the genus level, the intestinal flora had higher concentrations of Psychrobacter, Bacillus, Pseudomonas, Acinetobacter, and Macrococcus. In both shrimp species, the contents of Acinetobacter and Macrococcus were higher in spring than in winter. The most important potential functions of the intestinal microbiota were amino acid metabolism and purine metabolism. Additionally, the functions of metabolism and diseases in the intestinal microbiota of E. annandalei were greatly influenced by the season. Furthermore, the experimental results indicated that a lower ratio of Firmicutes to Bacteroidetes was associated with a larger body weight in shrimp. Overall, this study provides a theoretical reference for understanding the intestinal bacterial community of shrimp in estuaries and the healthy cultivation of E. annandalei and E. carinicauda.